Bilateral changes of TNF-alpha and IL-10 protein in the lumbar and cervical dorsal root ganglia following a unilateral chronic constriction injury of the sciatic nerve - Jancálek, Radim; Dubový, Petr; Svízenská, Ivana; Klusáková, Ilona (Journal of neuroinflammation, 2010)
BACKGROUND: There is a growing body of evidence that unilateral nerve injury induces bilateral response, the mechanism of which is not exactly known. Because cytokines act as crucial signaling molecules for response of peripheral nerves to injury, they may be induced to mediate the reaction in remote structures. METHODS: We studied levels of tumor necrosis factor alpha (TNF-alpha) and interleukin 10 (IL-10) proteins using ELISA in the ipsilateral and contralateral lumbar (L4-L5) and cervical (C7-C8) dorsal root ganglia (DRG) from naïve rats, rats operated on to create unilateral chronic constriction injury (CCI) of the sciatic nerve, and sham-operated rats. Withdrawal thresholds for mechanical allodynia and thermal hyperalgesia were measured in the ipsilateral and contralateral hind and forepaws. RESULTS: The ipsilateral hind paws of all rats operated upon for CCI displayed decreased withdrawal thresholds for mechanical allodynia and thermal hyperalgesia, while no significant behavioral changes were found in the contralateral hind paws and both forepaws. Significantly lower baseline levels of TNF-alpha and IL-10 protein were measured by ELISA in the lumbar than cervical DRG of naïve rats. Bilateral elevation of TNF-alpha was induced in both the lumbar and cervical DRG by unilateral CCI of the sciatic nerve for 7 and 14 days, while the level of IL-10 protein was increased bilaterally in the lumbar DRG 1 and 3 days after operation. IL-10 levels declined bilaterally even below baseline level in both cervical and lumbar DRG 7 days from CCI and normalized after 14 days. In contrast to no significant changes in TNF-alpha, level of IL-10 protein was significantly increased in the ipsilateral lumbar DRG after 3 days and bilaterally in the lumbar DRG after 14 days from sham operation. CONCLUSIONS: The results of our experiments show a bilateral elevation of TNF-alpha and IL-10 not only in the homonymous DRG but also in the heteronymous DRG unassociated with the injured nerve. This suggests that bilaterally increased levels of TNF-alpha and IL-10 in DRG following unilateral CCI are linked with general neuroinflammatory reaction of the nervous system to injury rather than only to development and maintenance of neuropathic pain.
Keywords: Constriction, Pathologic; nemoci sedacího nervu; práh bolesti; Functional Laterality; Lumbar Vertebrae; Female; analýza rozptylu; Interleukin-10; ELISA; Analysis of Variance; krysa rodu Rattus; spinální ganglia; Hyperalgesia; Sciatic Neuropathy; zvířata; Enzyme-Linked Immunosorbent Assay; potkani Wistar; TNF-alfa; bederní obratle; ženské pohlaví; Pain Threshold; funkční lateralita; Rats, Wistar; Rats; Tumor Necrosis Factor-alpha; hyperalgezie; Cervical Vertebrae; interleukin-10; Animals; Ganglia, Spinal; krční obratle; stenóza